Impact of MDR1 genetic polymorphisms on postoperative piritramide analgesia - Matouskova, O; Slanar, O; Adamkova, J; Pafko, P; Perlik, F; Adamek, S (Bratislavske lekarske listy, 2013)
OBJECTIVES: The aim of prospective study was to evaluate the therapeutic efficacy of piritramide in patients after removal of parathyroid glands in relation to MDR1 genotype. In the treatment of moderate acute postoperative pain, piritramide plays a major role. It is difficult to predict its optimal therapeutic efficacy and tolerability in individual patients. METHODS: We compared the effect of piritramide in 56 patients after surgical removal of parathyroid glands in a prospective study. We evaluated pain intensity, pain difference and sum of pain difference (SPID) using visual analogue scale (VAS in mm) and adverse effects in the relationship with the MDR1 - polymorphism of G2677T/A. RESULTS: In the wild-type group (2677GG), there was maximal pain difference of 30.6 ± 24.9 and SPID of 209.33 ± 95.80 while in genotype 2677TT and 2677GT, the corresponding values were 19.5 ± 25.5 and 147.07 ± 91.38, respectively. In group of patients with wild type of 2677GG genotype, there was 80 % of responders with more than 50 % reduction in VAS as compared to baseline while in group with carriers of 2677T allele, there are only 39 % of responders present (χ² = 5. 83; p = 0.016). Furthermore, the total consumption of piritramide was lower in comparison with the variant-allele carrying group (p = 0.008). The total incidence of adverse drug reactions was observed in 40 % of patients with wild type of 2677GG genotype when compared to 83% in the group carrying the variant allele (χ² = 7.92; p = 0.005). Significantly more patients in the wild-type group were satisfied with postoperative pain treatment in comparison to the variant allele group (χ² = 6. 49; p = 0.0109). CONCLUSION: We observed a better analgesic effect of piritramide and a decreased incidence of side effects in the wild-type genotype (2677GG) group, when compared with variant-allele carrying patients (Tab. 2, Fig. 1, Ref. 7).
Keywords: Pirinitramide; paratyreoidektomie; Pain Measurement; Humans; ATP Binding Cassette Transporter, Subfamily B, Member 1; lidé středního věku; pooperační bolest; polymorfismus genetický; pirinitramid; Female; lidé; Polymorphism, Genetic; Analgesics, Opioid; P-glykoprotein; ženské pohlaví; Parathyroidectomy; Male; Middle Aged; opioidní analgetika; Pain, Postoperative; mužské pohlaví; měření bolesti